PENGENDALIAN MUTU BIDANG MIKROBIOLOGI KLINIK - Prihatini Prihatini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
The quality control program in microbiology are procedures to identify microorganism,monitoring,to asses laboratory competencein handling clinical materials, other methods needed.QC is essential in bacteriology because nature, unlike clinical chemistry andhematology QC’s, because can’t compare with control value. The QC in microbiology include preparation of pra-analitics,analitics andpost-analitics which depending to personal, material,SOP and micoorganism Specimens, laboratory Instruments like incubators, freezer,autoclaves, must be good preparations. Examinations use control standard, monitoring all of themes periodically The laboratory resultswere recorded and evaluated as reference laboratory. The QC microbiology have been presented, they need large budgets to validity oflaboratory results.